The partner loans' multidisciplinary analysis: Portuguese's case study - Aldeia, Susana (2020)
This paper seeks to understand the framework of the loans from partners to the company in a multidisciplinary overview. In particular, it studies the accounting and taxation treatment of the loans from members to societies. For this purpose, it researches several data sources of Portugal: Portuguese Accounting Standards (Sistema de Normalização Contabilística - SNC), Value Added Tax (Imposto sobre o Valor Acrescentado - IVA), Corporate Income Tax (Imposto sobre o Rendimento das Pessoas Coletivas - IRC). The results show that, in the accounting domain, loans from business owners to entity meet the requirements to be considered financial liabilities. The financial position's statement presents it in the second element. Under the lending contract, the lender can receive interest or not. In the case of income receipt, it is subject to taxation in the beneficiary's sphere, and it constitutes a financial expense the borrower's realm. This operation is VAT exempt, according to article 9º. In the CIT, the interests are tax expense under some circumstances predicted in the tax law. The paper presents some limitations because it is restricted to Portugal jurisdiction; it could be interesting to analyse it in other countries.